Neurosurgery in morbidly obese patients - Mohanaselvi, S.; Subramanian, Rajkumar; Sardar, Arijit; Anand, Rahul; Agarwal, Anil; Khanna, Puneet (Journal of Neuroanaesthesiology and Critical Care, 2016)
Obesity has significant impact on various organ systems of the body and thus needs a well-planned anaesthetic management. Obese patients with multiple co morbidities are expected to have more complications than normal individuals. Obesity may influence the risk of aneurysm formation and rupture and/or the outcome of patients who have aneurysmal SAH. Most of the neurosurgeries require different patient positions for adequate exposure of surgical site. Moreover morbidly obese patient means a huge and heavy patient who will require bigger operating table and other accessories and their implications. Confusion regarding the risks and benefits of mechanical and pharmacological prophylaxis in neurosurgical patients for DVT with risks of major and minor haemorrhage still persists. The anesthetic concerns in an obese patient undergoing neurosurgery have not been studied so far. This review aims in discussing obesity in neurosurgical patients.
Keywords: Anaesthetic management; complications; morbid obesity; neurosurgery